Indications of a new antibiotic in clinical practice: results of the tigecycline initial use registry - Curcio,Daniel (2008)
Tigecycline is the first of a new class of antibiotics named glycylcyclines and it was approved for the treatment of complicated intra-abdominal infections and complicated skin and skin structure infections. Notwithstanding this, tigecycline's pharmacological and microbiological profile which includes multidrug-resistant pathogens encourages physicians' use of the drug in other infections. We analyzed, during the first months after its launch, the tigecycline prescriptions for 113 patients in 12 institutions. Twenty-five patients (22%) received tigecycline for approved indications, and 88 (78%) for "off label" indications (56% with scientific support and 22% with limited or without any scientific support). The most frequent "off label" use was ventilator associated pneumonia (VAP) (63 patients). The etiology of infections was established in 105 patients (93%). MDR-Acinetobacter spp. was the microorganism most frequently isolated (50% of the cases). Overall, attending physicians reported clinical success in 86 of the 113 patients (76%). Our study shows that the "off label" use of tigecycline is frequent, especially in VAP. due to MDR-Acinetobacter spp., where the therapeutic options are limited (eg: colistin). Physicians must evaluate the benefits/risks of using this antibiotic for indications that lack rigorous scientific support.